The Influence of Perioperative Antibiotic Prophylaxis on Wound Infection and on the Colonization of Wound Drains in Patients After Correction of Craniosynostosis - Holle, Johannes; Finger, Tobias; Lugonja, Julia; Schmidt, Florian; Schaumann, Andreas; Gratopp, Alexander; Thomale, Ulrich-Wilhelm; von Bernuth, Horst; Schulz, Matthias (Frontiers in Pediatrics, 2021)
Objective: Evidence for the duration of perioperative antibiotic prophylaxis (PAP) after the correction of craniosynostosis in children is scarce. We evaluated the necessary duration of PAP to ensure a minimal rate of postoperative wound infections. Methods: In this monocentric, retrospective, and prospective pilot study, two PAP protocols were compared. From August 2017 to May 2018, treatment group 1 (TG 1) was treated using the standard PAP protocol with at least three doses of antibiotics. Between May 2018 and March 2019, a shortened PAP with a single-shot administration was given to treatment group 2 (TG 2a and b). Endpoints of this study were wound infection rate, colonization rate of wound drains, and the course of treatment reflected by clinical and laboratory data. Results: A cohort of 187 children underwent craniosynostosis correction: 167 were treated according to protocols-−95 patients with at least three doses (TG 1) and 72 patients with a single-shot of cefuroxime (TG 2a). Baseline characteristics were similar for both groups. We could not detect significant differences, neither for wound infection rates (TG 1: 1.1%, TG 2a: 0.0%, p = 0.38) nor for colonization rates of wound drains (TG 1: 4.8%, TG 2a: 10.5%, p = 0.27). Conclusions: Single-shot PAP had no adverse effects on the wound infection rate or the colonization rate of the wound drains compared with prolonged perioperative antibiotic prophylaxis. As a result, single-shot preoperative PAP is now applied to the majority craniosynostosis patients undergoing surgical correction in our unit.